GALACTOSE OXIDASE NANOPARTICLES BASED NANOSENSOR FOR AMPEROMETRIC DETERMINATION OF GALACTOSE - MAMTA SHARMA; MINAKSHI SHARMA (International Journal of Pharma and Bio Sciences, 2016)
serum. The nanosensor comprises galactose oxidase nanoparticles immobilized directly on the surface of gold (Au) electrode as working electrode, Ag/AgCl as reference electrode and platinum (Pt) wire as an auxiliary electrode connected through potentiostat. The nanosensor showed an optimum response at pH 6.0 and temperature 30oC, when operated at a scan rate of 50 mv/s. The working range of the sensor was 0.1 to 20 mM, with a detection limit of 0.16 mM. The enzyme electrode was used many times over a period of 90 days, when stored at 4oC.The Nanosensor has an advantage over the earlier enzyme sensor in that the enzyme nanoparticles are more stable, sensitive and achieve higher self life during construction of nanosensor. The fabricated nanosensor was successfully employed for the determination of galactose in human blood serum.